A comment on Nishimura, Nakajima, and Kiyota's "Does the natural selection mechanism still work in severe recessions? Examination of the Japanese economy in the 1990s" - Tae Okada; Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2007)
Nishimura, Nakajima, and Kiyota (2005) analyze the entry/exit behavior patterns of Japanese firms during the 1990s and find that relatively efficient (high total factor productivity (TFP)) firms exited while relatively inefficient (low TFP) firms survived during the banking-crisis period of 1996-97. They conclude from this finding that the natural selection mechanism (NSM) apparently malfunctions during severe recessions, but we offer a much more plausible interpretation: the NSM continued to function effectively even during this period, but aberrant banking practices (in particular, 'forbearance lending' ('evergreening') and the 'forcible withdrawal of loans' and/or the 'reluctance to lend') caused a shift in the type of natural selection from 'directional selection' to 'disruptive selection,' with the most efficient (highest TFP) firms as well as the least efficient (lowest TFP) firms being favored and firms of intermediate efficiency and TFP being selected against.
Keywords: D21; D24; O47; L11; 330; Total factor productivity; Entry and exit; Natural selection; Directional selection; Disruptive selection; Evolution; Banking crisis; Forbearance lending; Forcible withdrawal of loans; Reluctance to lend; Credit crunch; Recession; Japanese economy; Japan; Produktivität; Konjunktur; Markteintritt; Marktaustritt; Japan